Analisis Prestasi Atlet PPLP Sumatera Barat Menggunakan Analisis Jalur - Charles, Denisha Aprilia (UNIVERSITAS NEGERI PADANG, 2025)
The West Sumatra Student Sport Education and Training Center serves as a training ground and coaching facility to improve sport achievement in West Sumatra. Athletes accomplishments are influenced by a wide range of elements, such as their passions, skills, families, environments, coaches, and motivation. The purpose of this research is to determine the factors direct and indirect influences. This study is an applied one that uses 111 participants as its sample and primary data. The results of the path analysis show that athlete achievement is directly influenced by the variables of physical quality (X1) and motivation variables (X6) . Indirectly, athlete achievement is influenced by the variables of the social environment (X2), athlete character (X3) through the variables of athlete physical quality (X1) , and the variables of the social environment (X2) , perception of the coach (X5) through the variable of athlete motivation (X6). In total, the achievement of athletes in PPLP West Sumatra is influenced by the variables of physical condition (X1) , motivation (X6), social environment (X2), athlete character (X3), and perception of the coach (X5).